1993
DOI: 10.1002/pros.2990230407
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cis‐4‐hydroxy‐L‐proline on the androgen‐lnduced growth of the prostate of the prepubertally castrated guinea pig

Abstract: The present study examined the effects of cis-4-hydroxy-L-proline (CHP), a proline analog, on the androgen-induced growth of the lateral prostate of prepubertally castrated guinea pigs. Prepubertal male guinea pigs were castrated at the age of 3 weeks and allowed to recover completely before subjection to an experimental regime to alter the stromal collagen synthesis by CHP. The animals were kept on a special proline-deficient diet (PDD) for a week before the subcutaneous injection of CHP (200 mg/kg/day) for 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2000
2000
2001
2001

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Early studies in castrated and pubertal rat prostates have demonstrated the importance of collagens in the growth regulation of prostate gland [9±12]. Its importance is further demonstrated by the studies of metabolic inhibition of collagen synthesis in the androgen-stimulated castrated prostates, and such inhibition can effectively prevent the growth of prostate [11,13,14], suggesting that the androgenstimulated growth of prostate is mediated by the stromal collagens. Tenascin, an extracellular matrix glycoprotein, is believed to play a role in epithelialstromal interactions in some hormone-dependent organs including prostate.…”
Section: Introductionmentioning
confidence: 99%
“…Early studies in castrated and pubertal rat prostates have demonstrated the importance of collagens in the growth regulation of prostate gland [9±12]. Its importance is further demonstrated by the studies of metabolic inhibition of collagen synthesis in the androgen-stimulated castrated prostates, and such inhibition can effectively prevent the growth of prostate [11,13,14], suggesting that the androgenstimulated growth of prostate is mediated by the stromal collagens. Tenascin, an extracellular matrix glycoprotein, is believed to play a role in epithelialstromal interactions in some hormone-dependent organs including prostate.…”
Section: Introductionmentioning
confidence: 99%